Following his own path : Li Zehou and contemporary Chinese thought - Rošker, Jana, 1960- (State University of New York, 2019)
"In this book, Jana S. Rošker offers the first comprehensive overview and exegesis of the work of Li Zehou, who is one of the most significant and influential Chinese philosophers of our time. Rošker shows us how Li's complex system of thought seeks to revive various Chinese traditions, and at the same time attempts to harmonize or reconcile this cultural heritage with the demands of the dominant economic, political, and axiological structures of our globalized world. Variously characterized as "neo-traditional," "neo-Kantian," "post-Marxist," "Marxist-Confucian," "pragmatist," "instrumentalist," "romantic," and more, Li's work was central to the period known as the Chinese Enlightenment in the 1980s and has helped modify and transform antiquated patterns of Chinese intellectual discourse. He is one of the rare Chinese thinkers whose work has had not only had a deep and lasting impact on Chinese intellectuals, but has acquired a broad readership outside of China as well. Seen from a broader intercultural perspective, Li's unique and imaginative approach to a wide range of basic theoretical problems has created new styles of intellectual investigation, while reminding us of our belonging to a common humanity, regardless of differences in our individual cultures, languages, preferences, and traditions"-- Provided by publisher.
Keywords: Li, Zehou.; Li, Zehou; Philosophy, Chinese -- 20th century.; Philosophy, Chinese -- 21st century.; Philosophie chinoise -- 21e siècle.; PHILOSOPHY -- Eastern.; Philosophy, Chinese; 1900-2099